PENGARUH STRATEGI QUESTION ANSWER RELATIONSHIP TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Fiantika, Hilda; Taufik, Taufina; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aims to determine the influence of Question Answer Relationship (QAR) strategy on the comprehension skills of primary school students. This type of research is quasi experiment in the form of Non-Equivalent Postest-Only Control Group Design. The population of this research is all students of Grade VI of Elementary School of Sapih River Cluster. With sample cluster random sampling technique that is as much as 8 SD. After the normality and homogeneity test, in all schools have normal data. So the researchers classify (cluster) population that can be sampled is a school with normal data and homogeneous, that is as much as 4 schools. Then the draw was made and it was found that SDN 27 Sungai Sapih was the sample for the researcher. Data analysis was done by using lilifors test. The results showed that there is an influence of QAR strategy on reading comprehension skills of grade 6 students of SDN 27 Sungai Sapih Padang. This is evidenced from the t-test (t-test) with a significant level α = 5% obtained tcount (9.0824)> ttable (2.0106) so that H1 is accepted. Keywords: Question Answer Relationship (QAR) strategy, reading comprehension